2008
DOI: 10.1016/j.eatbeh.2007.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Features associated with diet pill use in individuals with eating disorders

Abstract: We investigated the relation between diet pill use and eating disorder subtype, purging and other compensatory behaviors, body mass index (BMI), tobacco and caffeine use, alcohol abuse or dependence, personality characteristics, and Axis I and Axis II disorders in 1,345 participants from the multisite Price Foundation Genetics Studies. Diet pill use was significantly less common in women with restricting type of AN than in women with other eating disorder subtypes. In addition, diet pill use was associated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 32 publications
3
11
0
Order By: Relevance
“…Consistent with previous research (Reba-Harrelson et al , 2008; Roerig et al , 2003), diet pill use was elevated in all ED groups. The ANBN group was at particularly elevated risk (i.e., approximately 15 times more likely than the referent).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Consistent with previous research (Reba-Harrelson et al , 2008; Roerig et al , 2003), diet pill use was elevated in all ED groups. The ANBN group was at particularly elevated risk (i.e., approximately 15 times more likely than the referent).…”
Section: Discussionsupporting
confidence: 91%
“…The ANBN group was at particularly elevated risk (i.e., approximately 15 times more likely than the referent). Diet pill use has been associated with purging, novelty seeking, and several Axis I and Axis II disorders (Reba-Harrelson et al , 2008) which could explain why both the BN and ANBN groups, who tend to score higher on measures of novelty seeking (Cassin & von Ranson, 2005; Fernandez-Aranda et al , 2006; Reba et al , 2005), reported more use than the AN group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The characteristics of individuals with different compensatory behaviors, such as exercise, vomiting, laxative use, and diet pill use, have been studied in eating disorder (ED) patients [18][19][20][21][22]. Notably, laxative abuse is most frequently associated with greater general psychopathology, self-injurious behavior, suicide attempts, history of depression and anxiety, borderline personality features, and greater eating symptomatology [22].…”
Section: Introductionmentioning
confidence: 98%
“…28 Diet pill use was among the compulsive weight-control behaviors and types of substance abuse seen in 1345 women. 29 Treatment for alcohol dependence may lead to reduction of eating pathology. 30 Therefore, screening for all types of substance abuse is advised for patients with eating disorders.…”
Section: Clinical Criteria Of the Major Types Of Eating Disorders *mentioning
confidence: 99%